A common fixed point theorem for two sequences of self-mappings - Takeshi Taniguchi (International Journal of Mathematics and Mathematical Sciences)
In this paper a common fixed point theorem for two sequences of self-mappings from a complete metric space M to M is proved. Our theorem is a generalization of Hadzic's fixed point theorem[1].